About Riesz theory of compact operators - Sah, Nagendra Pd (BIBECHANA, 2012)
In this paper, it is shown that every compact operators are bounded and continuous. The bounded and continuous properties of an operator is sufficient for a Riesz operator. For mapping T: K-?I in normed linear space with some extended [1] properties, T becomes compact. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7186 BIBECHANA 9 (2013) 126-129